2016
DOI: 10.1242/dmm.025874
|View full text |Cite
|
Sign up to set email alerts
|

Development of a subset of forelimb muscles and their attachment sites requires the ulnar-mammary syndrome gene Tbx3

Abstract: In the vertebrate limb over 40 muscles are arranged in a precise pattern of attachment via muscle connective tissue and tendon to bone and provide an extensive range of motion. How the development of somite-derived muscle is coordinated with the development of lateral plate-derived muscle connective tissue, tendon and bone to assemble a functional limb musculoskeletal system is a long-standing question. Mutations in the T-box transcription factor, TBX3, have previously been identified as the genetic cause of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 49 publications
1
57
0
Order By: Relevance
“…New insight into this process comes from a recent study, which identified a role for the T-box transcription factor Tbx3 in the patterning of two muscles in the forelimb, along with their skeletal attachment sites (Colasanto et al, 2016). Deletion of Tbx3 in limb mesenchyme by Prx1Cre results in loss of all three bone eminences.…”
Section: Enthesesmentioning
confidence: 99%
See 4 more Smart Citations
“…New insight into this process comes from a recent study, which identified a role for the T-box transcription factor Tbx3 in the patterning of two muscles in the forelimb, along with their skeletal attachment sites (Colasanto et al, 2016). Deletion of Tbx3 in limb mesenchyme by Prx1Cre results in loss of all three bone eminences.…”
Section: Enthesesmentioning
confidence: 99%
“…In the mouse limb, Tcf4 is expressed early in lateral plate mesoderm, at ~E9.5 (Colasanto et al, 2016). By E12.5, Tcf4+ MCT cells are closely associated with but distinct from Pax7+ and MyoD+ myogenic cells (Mathew et al, 2011).…”
Section: Tcf4mentioning
confidence: 99%
See 3 more Smart Citations